The Bishop, between pastor and judge in the ius antiquum - Belda Iniesta, Javier (Prawo Kanoniczne, 2023)
Recenty, the emergence of the so-called brevior process, which has been entrusted to the Bishop by the Legislator, has highlighted the mission of administer justice to the successors of the Apostles. However, this is not a novelty: the Church, since it was founded by Christ, has needed to face the problems of every society. One of them was the judicial activity, a consequence of conflicts caused by the human condition and the delay of parusity. The bishop, from the beginning, assumed this role, which he had to combine with his work as a shepherd of souls. Our work is a study of how this work unfolded in the early centuries of the Church, both internally and then as part of the Empire. In order to reach this objetive, we have proceeded to study the early canonical sources that report this judicial activity and the constantine's legislation on Audientia episcopalis, when the Church abandoned clandestineness and found its place alongside the Empire.